PENGARUH KOMUNIKASI INTERPERSONAL GURU DAN LINGKUNGAN SEKOLAH TERHADAP HASIL BELAJAR SISWA SD NEGERI DI KELURAHAN BUKIT SANGKAL KECAMATAN KALIDONI PALEMBANG - Mardaleni Mardaleni; Syarwani Ahmad; Pahlawan Pahlawan (Jurnal Manajemen Pendidikan, 2026)
Primary education plays a strategic role in developing students’ cognitive abilities, attitudes, and skills. Students’ learning outcomes, as an indicator of educational success, are influenced by various internal and external factors. Two external factors considered to have a significant influence are teachers’ interpersonal communication and the school environment. This study aims to examine and analyze the effect of teachers’ interpersonal communication and the school environment, both partially and simultaneously, on students’ learning outcomes at public elementary schools in Bukit Sangkal Subdistrict, Kalidoni District, Palembang. This study employed a quantitative approach with a correlational research design. The population consisted of all teachers of grades IV, V, and VI at public elementary schools in Bukit Sangkal Subdistrict, totaling 58 teachers, who were all included as research samples. Data on teachers’ interpersonal communication and the school environment were collected through questionnaires, while students’ learning outcomes were obtained from report card scores for the even semester of the 2024/2025 academic year. Data analysis techniques included prerequisite tests, Pearson correlation analysis, simple linear regression, and multiple linear regression. The results of the study indicate that teachers’ interpersonal communication has a significant effect on students’ learning outcomes. The school environment also has a significant effect on students’ learning outcomes.